A noção do desperdício: narrativas docentes em três níveis do ensino básico - Vieira, Jairo Brasil (Universidade do Vale do Rio do Sinos, 2008)
This research is the result from an anxiety of the author. It was brought from the Post-Graduation in History, carried out in 2004, in Brasília, when he had contact with authors of the environmental history and with more expanded concepts of environmental education. In the elaboration of the final monograph the researcher could understand that there is identification between history science and environmental education by the choice of an important and controversial character of the Brazilian life as central theme: José Antonio Lutzenberger. The involvement with the history of the environmentalist Lutzenberger provided some uneasiness, among them, how education can change environmental issues, which are crucial when the results of the human being action on the natural resources that the planet gives for the humanity are evaluated. As an academic student at UNISINOS, in the Post-Graduation Program in Education, the researcher tried to understand how he could elaborate proposals for a transforming curriculum of
Keywords: currículo; educação ambiental; educação básica; recursos naturais; desperdício; basic education; curriculum; environmental education; natural resources; wastefulness; Ciências Humanas